Jane Addams in the classroom - Schaafsma, David, 1953- (University of Illinois Press, 2014)
The essays in Jane Addams in the Classroom explore how Addams's life, work, and philosophy provide invaluable lessons for teachers seeking connection with their students. The collection examines Addams's emphasis on listening to and learning from those around her and encourages contemporary educators to connect with students.